Mantle helium along the Newport‐Inglewood fault zone, Los Angeles basin, California: A leaking paleo‐subduction zone. (26th July 2015) - Boles, J. R.; Garven, G.; Camacho, H.; Lupton, J. E.
Abstract Mantle helium is a significant component of the helium gas from deep oil wells along the Newport‐Inglewood fault zone (NIFZ) in the Los Angeles (LA) basin. Helium isotope ratios are as high as 5.3 Ra (Ra = 3He/4He ratio of air) indicating 66% mantle contribution (assuming R/Ra = 8 for mantle), and most values are higher than 1.0 Ra. Other samples from basin margin faults and from within the basin have much lower values (R/Ra < 1.0). The 3He enrichment inversely correlates with CO2, a potential magmatic carrier gas. The δ13C of the CO2 in the 3He rich samples is between 0 and −10‰, suggesting a mantle influence. The strong mantle helium signal along the NIFZ is surprising considering that the fault is currently in a transpressional rather than extensional stress regime, lacks either recent magma emplacement or high geothermal gradients, and is modeled as truncated by a proposed major, potentially seismically active, décollement beneath the LA basin. Our results demonstrate that the NIFZ is a deep‐seated fault directly or indirectly connected with the mantle. Based on a 1‐D model, we calculate a maximum Darcy flow rate q ∼ 2.2 cm/yr and a fault permeability k ∼ 6 × 10−17 m2 (60 microdarcys), but the flow rates are too low to create a geothermal anomaly. The mantle leakage may be a result of the NIFZ being a former Mesozoic subduction zone in spite of being located 70 km west of the current plate boundary at the San Andreas fault.